PERBANDINGAN METODE AVERAGE LINKAGE DAN K-MEANS DALAM MENGELOMPOKKAN PERSEBARAN PENYAKIT MULUT DAN KUKU DI INDONESIA - Angelina; Harsyiah, Lisa; Purnamasari, Nur Asmita (Jurusan Matematika, Fakultas Teknik, Universitas Bangka Belitung, 2024)
The purpose of this study was to analyze the spread of Foot and Mouth Disease (FMD in Indonesia by using two different methods: average linkage and k-means. In addition, this study also aimed to determine the most effective method of classifying the distribution of FMD in Indonesia between the two methods used. The results of cluster validation showed that the optimal number of clusters formed in the average linkage method was 4, while in the k-means method, there were 3 clusters. The grouping with the average linkage method was better than the results of classifying with the k-means method, as the standard deviation ratio in the average linkage method was smaller at 0,035, compared to 0,258 in the k-means method. Therefore, it was concluded that the average linkage method was better than the k-means method in classifying the distribution of FMD in Indonesia.